Discovery of Arylfuran and Carbohydrate Derivatives from the BraCoLi Library as Potential Zika Virus NS3pro Inhibitors - Fernanda Kelly Marcelino e Oliveira; Beatriz Murta Rezende Moraes Ribeiro; Ellen Gonçalves de Oliveira; Marina Mol Sena Andrade Verzola; Thales Kronenberger; Vinícius Gonçalves Maltarollo; Ricardo José Alves; Renata Barbosa de Oliveira; Rafaela Salgado Ferreira; Jônatas Santos Abrahão; Mateus Sá Magalhães Serafim (Future Pharmacology)
Background/Objectives: Zika fever is a disease caused by the Zika virus (ZIKV). Symptomatic cases may be associated with neurological disorders in adults, as well as congenital Zika syndrome and other birth defects during pregnancy. In 2016, Zika fever was considered a public health problem by the World Health Organization (WHO), highlighting the need to develop new therapies against the disease. Currently, there is no antiviral or vaccine available to treat or prevent severe cases. Due to the lack of available therapeutics and few promising hit molecules, we computationally screened the well-described ZIKV protease (NS3pro) as a drug target to revisit the small-molecule database Brazilian Compound Library (BraCoLi) and select potential inhibitors. Methods: We employed a consensus docking screening of a library of 1176 compounds using GOLD and DockThor. We selected 28 hits based on predicted binding affinity, and only the remnants of three compounds were available in the library at the time of this study for experimental validation. The hits were evaluated for their cytotoxic (CC50) and effective concentrations (EC50) for their potential antiviral activity in Vero cells. Results: The three hit compounds presented modest CC50 values of 89.15 ± 3.72, >100, and 29.67 ± 1.01 μM, with the latter, a carbohydrate derivative, having an EC50 value of >12.5 μM (~40% inhibition) against ZIKV PE243. Additionally, the essentially non-toxic compound, an arylfuran derivative, also inhibited the ZIKV NS3pro with an IC50 value of 17 μM but presented evidence of acting through a promiscuous mechanism for enzyme inhibition. Conclusion: This study highlights the relevance of revisiting existing small-molecule assets to identify novel therapeutic starting points against ZIKV, aiming for potential lead candidates in the future.